Composite power semiconductor switches for high-power applications - Mathieson, Ross Ellis (The University of Edinburgh, 2021)
It is predicted that 80 % of the world’s electricity will flow through power electronic based converters by 2030, with a growing demand for renewable technolo gies and the highest levels of efficiency at every stage from generation to load. At the heart of a power electronic converter is the power semiconductor switch which is responsible for controlling and modulating the flow of power from the input to the output. The requirements for these power semiconductor switches are vast, and include: having an extremely low level of conduction and switching losses; being a low source of electromagnetic noise, and not being susceptible to external Electromagnetic Interference (EMI); and having a good level of ruggedness and reliability. These high-performance switches must also be economically viable and not have an unnecessarily large manufacturing related carbon footprint. This thesis investigates the switching performance of the two main semiconductor switches used in high-power applications — the well-established Silicon (Si)-Insulated-Gate Bipolar Transistor (IGBT) and the state-of-the-art Wide-Bandgap (WBG) Silicon-Carbide (SiC)-Metal–Oxide–Semiconductor Field-Effect Transistor (MOSFET). The SiC-MOSFET is ostensibly a better device than the Si-IGBT due to the lower level of losses, however the cost of the device is far greater and there are characteristics which can be troublesome, such as the high levels of oscillatory behaviour at the switching edges which can cause serious Electromagnetic Compatibility (EMC) issues. The operating mechanism of these devices, the materials which are used to make them, and their auxiliary components are critically analysed and discussed. This includes a head-to-head comparison of the two high-capacity devices in terms of their losses and switching characteristics. The design of a high-power Double-Pulse Test Rig (DPTR) and the associated high-bandwidth measurement platform is presented. This test rig is then extensively used throughout this thesis to experimentally characterise the switching performance of the aforementioned high-capacity power semiconductor devices. A hybrid switch concept — termed “The Diverter” — is investigated, with the motivation of achieving improved switching performance without the high-cost of a full SiC solution. This comprises a fully rated Si-IGBT as the main conduction device and a part-rated SiC-MOSFET which is used at the turn-off. The coordinated switching scheme for the Si/SiC-Diverter is experimentally examined to determine the required timings which yield the lowest turn-off loss and the lowest level of oscillatory behaviour and other EMI precursors. The thermal stress imposed on the part-rated SiC-MOSFET is considered in a junction temperature simulation and determined to be negligible. This concept is then analysed in a grid-tied converter simulation and compared to a fully rated SiC-MOSFET and Si-IGBT. A conduction assistance operating mode, which solely uses the part-rated SiC-MOSFET when within its rating, is also investigated. Results show that the Diverter achieves a significantly lower level of losses compared to a Si-IGBT and only marginally higher than a full SiC solution. This is achieved at a much lower cost than a full SiC solution and may also provide a better method of achieving high-current SiC switches
Keywords: power semiconductor switchs; EMI; IGBT; SiC-MOSFET; Double-Pulse Test Rig; hybrid switch concept